5G NETWORK TRAFFIC CLASSIFICATION SYSTEM USING STACKING MACHINE LEARNING BASED ON NETWORK MONITORING TOOLS DATA - Rugayyah Alhaddad, Syamira
The 5G network requires a traffic management system capable of accurately